Randomized pilot study to disseminate caries-control services in dentist offices - Reynolds Debra; Anderson Maxwell; del Aguila Michael A; Spiekerman Charles; Grembowski David; Ellersick Allison; Foster James; Choate Leslie (BMC, 2006)
Abstract Background To determine whether education and financial incentives increased dentists' delivery of fluoride varnish and sealants to at risk children covered by capitation dental insurance in Washington state (U.S.). Methods In 1999, 53 dental offices in Washington Dental Service's capitation dental plan were invited to participate in the study, and consenting offices were randomized to intervention (n = 9) and control (n = 10) groups. Offices recruited 689 capitation children aged 6-14 and at risk for caries, who were followed for 2 years. Intervention offices received provider education and fee-for-service reimbursement for delivering fluoride varnish and sealants. Insurance records were used to calculate office service rates for fluoride, sealants, and restorations. Parents completed mail surveys after follow-up to measure their children's dental utilization, dental satisfaction, dental fear and oral health status. Regression models estimated differences in service rates between intervention and control offices, and compared survey measures between groups. Results Nineteen offices (34%) consented to participate in the study. Fluoride and sealant rates were greater in the intervention offices than the control offices, but the differences were not statistically significant. Restoration rates were lower in the intervention offices than the control offices. Parents in the intervention group reported their children had less dental fear than control group parents. Conclusion Due to low dentist participation the study lacked power to detect an intervention effect on dentists' delivery of caries-control services. The intervention may have reduced children's dental fear.